Billiards-related dystonia: A new task-specific dystonia. (March 2019) - Smilowska, Katarzyna; Domingos, Josefa; Pasman, Jaco W.; van Wamelen, Daniel J.; van de Warrenburg, Bart P.; Bloem, Bastiaan R.
Abstract: We report the first videotaped case of focal and task-specific dystonia of the upper limb that occurred exclusively while using a cue during billiard playing. The repetitive movements in conjunction with a highly skilled performance likely contributed to the development of this focal dystonia.